Ismael Quiles, Qué es el yoga, Colección Esquemas, Editorial Columba, Buenos Aires, 1970, 151 pp - Lértora Mendoza, Celina A. (1973)
Fil: Lértora Mendoza, Celina A. Fundación para el Estudio del Pensamiento; Argentina